2013
DOI: 10.4161/cc.25402
|View full text |Cite
|
Sign up to set email alerts
|

In vivo functional studies of tumor-specific retrogene NanogP8 in transgenic animals

Abstract: The current study was undertaken to investigate potential oncogenic functions of NanogP8, a tumor-specific retrogene homolog of Nanog (expressed in pluripotent cells), in transgenic animal models. To this end, human primary prostate tumor-derived NanogP8 was targeted to the cytokeratin 14 (K14) cellular compartment, and two lines of K14-NanogP8 mice were derived. The line 1 animals, expressing high levels of NanogP8, experienced perinatal lethality and developmental abnormalities in multiple organs, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 51 publications
(91 reference statements)
0
30
0
Order By: Relevance
“…23 By expressing a Nanog pseudogene NANOGP8 in the mouse skin, it inhibits the skin tumorigenesis induced by chemical carcinogen, suggesting that Nanog might be a tumor suppressor. 33 Our findings that Nanog activates p53 in the skin cells to induce the differentiation of progenitor cells could explain this apparent discrepancy. In this context, when compared with other tissues, skin has a distinct response to the ectopic expression of oncogene, namely oncogene-induced differentiation response for avoiding tumorigenesis.…”
Section: Nanog Induces Dna Dsb Damage and Inactivates Kap1mentioning
confidence: 77%
“…23 By expressing a Nanog pseudogene NANOGP8 in the mouse skin, it inhibits the skin tumorigenesis induced by chemical carcinogen, suggesting that Nanog might be a tumor suppressor. 33 Our findings that Nanog activates p53 in the skin cells to induce the differentiation of progenitor cells could explain this apparent discrepancy. In this context, when compared with other tissues, skin has a distinct response to the ectopic expression of oncogene, namely oncogene-induced differentiation response for avoiding tumorigenesis.…”
Section: Nanog Induces Dna Dsb Damage and Inactivates Kap1mentioning
confidence: 77%
“…The ability of GFP+ cells to form tumorspheres demonstrated that enriching for GFP+ cells more specifically isolated self‐renewing TNBC CSCs than the use of other paradigms, including enrichment by CD24 − /CD44+, CD49f hi , and ALDH + . We also show that our model based on the promoter activity of the embryonic stem cell transcription factor NANOG has the conceptual advantage of being able to define and functionally characterize CSCs in a more rigorous manner compared with the other established paradigms . The reporter system that we have developed tracks NANOG promoter activity.…”
Section: Discussionmentioning
confidence: 95%
“…A causal role of NANOG in tumorigenesis has been demonstrated not only by loss- and gain-of-function studies in cancer cells [1, 3, 9] but also by, recently, CRISPR/Cas9-mediated knockout [31] and genetic mouse model [28, 32, 33,34] studies. In addition to constitutive expression of NANOG in a small subset of cancer cells, NANOG may also be induced by tumor microenvironments such as inflammatory cytokines and hypoxia [27, 30, 35].…”
Section: Discussionmentioning
confidence: 99%